Extracellular vesicles and their cells of origin: Open issues in autoimmune diseases - Haghighitalab, Azadeh; Dominici, Massimo; Matin, Maryam M.; Shekari, Faezeh; Ebrahimi Warkiani, Majid; Lim, Rebecca; Ahmadiankia, Naghmeh; Mirahmadi, Mahdi; Bahrami, Ahmad Reza; Bidkhori, Hamid Reza (Frontiers in Immunology, 2023)
The conventional therapeutic approaches to treat autoimmune diseases through suppressing the immune system, such as steroidal and non-steroidal anti-inflammatory drugs, are not adequately practical. Moreover, these regimens are associated with considerable complications. Designing tolerogenic therapeutic strategies based on stem cells, immune cells, and their extracellular vesicles (EVs) seems to open a promising path to managing autoimmune diseases' vast burden. Mesenchymal stromal/stem cells (MSCs), dendritic cells, and regulatory T cells (Tregs) are the main cell types applied to restore a tolerogenic immune status; MSCs play a more beneficial role due to their amenable properties and extensive cross-talks with different immune cells. With existing concerns about the employment of cells, new cell-free therapeutic paradigms, such as EV-based therapies, are gaining attention in this field. Additionally, EVs’ unique properties have made them known as smart immunomodulators and are considered a potential substitute for cell therapy. This review provides an overview of the advantages and disadvantages of cell-based and EV-based methods for treating autoimmune diseases. The study also presents an outlook on the future of EVs to be implemented in clinics for autoimmune patients.